2010
DOI: 10.1002/jbmr.302
|View full text |Cite
|
Sign up to set email alerts
|

Impact of maturational status on the ability of osteoblasts to enhance the hematopoietic function of stem and progenitor cells

Abstract: Osteoblasts (OBs) exert a prominent regulatory effect on hematopoietic stem cells (HSCs). We evaluated the difference in hematopoietic expansion and function in response to co-culture with OBs at various stages of development. Murine calvarial OBs were seeded directly (fresh) or cultured for 1, 2, or 3 weeks prior to seeding with 1000 Lin-Sca1 + cKit+ (LSK) cells for 1 week. Significant increases in the following hematopoietic parameters were detected when comparing co-cultures of fresh OBs to co-cultures cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 71 publications
3
55
0
Order By: Relevance
“…CD166 expression on Stro-1 1 stromal cells 9 and binding of hematopoietic cells via CD166 to a yolk sacderived stromal cell line were also demonstrated. 10 These, and our data 2,4,5,11 confirmed that CD166 is expressed on hematopoietic progenitors and on OB, suggesting the unique possibility that these cells may interact with one another through CD166-CD166 interactions.…”
Section: Introductionsupporting
confidence: 73%
“…CD166 expression on Stro-1 1 stromal cells 9 and binding of hematopoietic cells via CD166 to a yolk sacderived stromal cell line were also demonstrated. 10 These, and our data 2,4,5,11 confirmed that CD166 is expressed on hematopoietic progenitors and on OB, suggesting the unique possibility that these cells may interact with one another through CD166-CD166 interactions.…”
Section: Introductionsupporting
confidence: 73%
“…Two studies have suggested that HSC-supporting cells are osteocalcin ϩ osteoblasts, based on immunofluorescence data demonstrating the proximity of HSCs to these cells. 18,27 Several studies have recently isolated cells of the osteoblastic lineage [28][29][30] and, whereas some results have suggested that hematopoietic progenitors are preferentially supported by immature osteoblastic cells, 29,31 others found that multiple fractions within the osteoblastic lineage could support HSCs, at least in vitro. 28,30 Data on the effects of osteoblastic deficiency induced in a transgenic mouse model expressing herpesvirus thymidine kinase gene under the control of a 2.3-kb fragment of the rat collagen-␣1 type I gene promoter suggest that osteoblastic cells targeted by this promoter, as well as their osteoblastic and osteocytic progeny, comprise the pool of osteoblastic cells capable of HSC regulation and support.…”
Section: Discussionmentioning
confidence: 99%
“…28,30 Data on the effects of osteoblastic deficiency induced in a transgenic mouse model expressing herpesvirus thymidine kinase gene under the control of a 2.3-kb fragment of the rat collagen-␣1 type I gene promoter suggest that osteoblastic cells targeted by this promoter, as well as their osteoblastic and osteocytic progeny, comprise the pool of osteoblastic cells capable of HSC regulation and support. 32 Ex vivo coculture systems designed to specifically identify HSC-supportive cell subsets [28][29][30][31] have not been evaluated for osteocytic signals and, given the mode and duration of coculture, are not likely to include osteocytic-type cells. Because, in TG mice, the osteocyte population is greatly expanded 8 and HSC support is decreased, the results of the current study also suggest that osteocytes are likely not a regulatory component of the HSC niche.…”
Section: Discussionmentioning
confidence: 99%
“…That basal Prg4 mRNA expression was higher in less differentiated osteoblastic cell cultures suggests that more immature osteoblastic cells are a primary source of proteoglycan 4 in the bone marrow. Considering that more immature osteoblastic cells have been implicated in HPC expansion and function, 43 the finding that basal Prg4 mRNA expression is higher in less differentiated osteoblastic cell cultures suggests that proteoglycan 4 may be involved in the mechanism by which more immature osteoblastic cells support HPCs.…”
Section: Discussionmentioning
confidence: 99%